1988
DOI: 10.3177/jnsv.34.363
|View full text |Cite
|
Sign up to set email alerts
|

The effects of orally administered linoleic acid and its autoxidation products on intestinal mucosa in rat.

Abstract: SummaryLinoleic acid and its autoxidation products , hydroperoxides and their secondary products, were orally administered to rats (350mg each/rat). Hemorrhage was seen in the alimentary canal at 6h after the dose of hydroperoxides. To examine their toxicities on intestinal mucosa , the activities of mucous enzymes (sucrase, maltase , and alkaline phos phatase) were measured. Hydroperoxides and their secondary products decreased the enzyme activities in jejunum at 6h after the doses and increased them in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…The observed 9 % reduction in BW gain (when comparing 0 and 12 d of peroxidation) was largely the result of reduced feed intake (7 % reduction when comparing 0 and 12 d), but it could also be related to enterocyte dysfunction, oxidative stress and so on. Kanazawa et al (7) concluded that lipid peroxidation impaired the functionality of the intestine as indicated by decreased enzyme activity (sucrase, maltase and alkaline phosphatase) in the jejunum and ileum after oral administration of products of peroxidation of linoleic acid to rats. In the current study, the improvement in daily BW gain because of the addition of unexposed soyabean oil when compared with the control diet was progressively diminished as the degree of peroxidation increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed 9 % reduction in BW gain (when comparing 0 and 12 d of peroxidation) was largely the result of reduced feed intake (7 % reduction when comparing 0 and 12 d), but it could also be related to enterocyte dysfunction, oxidative stress and so on. Kanazawa et al (7) concluded that lipid peroxidation impaired the functionality of the intestine as indicated by decreased enzyme activity (sucrase, maltase and alkaline phosphatase) in the jejunum and ileum after oral administration of products of peroxidation of linoleic acid to rats. In the current study, the improvement in daily BW gain because of the addition of unexposed soyabean oil when compared with the control diet was progressively diminished as the degree of peroxidation increased.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the effects of lipid peroxidation in the small intestine is particularly important because intestinal epithelial cells experience greater exposure to lipid peroxidation products. Early research provided evidence of the toxicity of peroxidised lipid products ( 6 , 7 ) and cautioned their use in livestock feeds because this could result in a reduction of productivity ( 8 , 9 ) . Recent studies investigated the deleterious effects of hydroperoxides, aldehydes and other lipid peroxidation subproducts on intestinal cell lines ( 2 , 10 ) and animals ( 7 , 11 , 12 ) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As to effects of hydroperoxides on intestinal mucosa, Kanazawa and coworkers (Kanazawa et al 1988) examined their potential toxicity by measuring activities of sucrase, maltase, and alkaline phosphatase, which refl ect the integrity and function of the brush border membrane. They found that hydroperoxides decreased enzyme activities in jejunum and ileum.…”
Section: Enzymatic Hydrolysis and Absorption Of Oxidized Dietary Lipidsmentioning
confidence: 99%
“…Esto explicaría la mejora observada por Thacker (23) cuando micronizó la canola integral. Finalmente, otra posible causa es la presencia de grasa peroxidada, porque afecta la capacidad de absorción del intestino delgado y modifica la morfología intestinal al alterar el potencial redox a nivel luminal (30) , afectando in vivo la membrana del enterocito, e in vitro la actividad de las enzimas sacarasa, maltasa y fosfatasa alcalina (31) . La molienda de la semilla de canola pudo favorecer este efecto porque no se utilizaron antioxidantes durante ese proceso.…”
unclassified